PENINGKATAN KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI TERHADAP MENTAL HEALTH SERTA KINERJA KARYAWAN DI PT.SUMBER ALFARIA TRIJAYA TBK CABANG PEDURUNGAN SEMARANG - Bayu Firman Syah; Mutamimah; Tri Wikaningrum (Universitas Duta Bangsa Surakarta, 2025)
This study aims to analyze the influence of transformational leadership and organizational culture on mental health and its implications for employee performance at PT. Sumber Alfaria Trijaya Tbk, Pedurungan Branch, Semarang. The research is grounded in the importance of human resources in facing increasingly competitive business environments, emphasizing the need for effective leadership and a conducive organizational culture to support employee well-being and optimize performance. The study uses a quantitative approach with explanatory research. Data were collected through questionnaires distributed to 100 employees from several Alfamart branches in the Pedurungan area. Data analysis was conducted using SPSS, including validity tests, reliability tests, multiple linear regression analysis, and mediation testing using the Sobel test. The results show that transformational leadership and organizational culture have a positive and significant influence on mental health, which in turn affects employee performance. Moreover, mental health is proven to mediate the effect of transformational leadership and organizational culture on performance. The implications of this study highlight the importance of strengthening leadership style and fostering a healthy organizational culture to create a supportive work environment that enhances employee performance.